Bifunctional N-heterocyclic carbene ligands for Cu-catalyzed direct C–H carboxylation with CO2. Issue 83 (13th November 2017) - Park, Da-Ae; Ryu, Ji Yeon; Lee, Junseong; Hong, Sukwon
Abstract : A copper-catalyzed direct C–H carboxylation of heteroarene compounds using diethylene glycol-functionalized imidazo[1, 5, a ] pyridin-3-ylidene (DEG-ImPy) ligands has been developed. Abstract : Diethylene glycol-functionalized imidazo[1, 5- a ]pyridin-3-ylidenes (DEG-ImPy) have been developed as bifunctional N-heterocyclic carbene ligands. The DEG-ImPy Cu(i ) complexes efficiently catalyzed the direct C–H carboxylation of benzoxazole with CO2, showing higher isolated yields than those with the N, N ′-(2, 6-diisopropylphenyl)imidazolylidene Cu catalyst.